1999
DOI: 10.1038/sj.ejcn.1600849
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breakfast cereal on diet and serum cholesterol: a randomized trial in North Karelia, Finland

Abstract: Objective: To test the hypothesis that a high carbohydrate breakfast with breakfast cereal leads to a meaningful reduction in dietary energy intake from fat, especially from saturated fat, and thus lower serum cholesterol levels.Design: An open randomized controlled cross-over trial. The subjects were randomized into intervention breakfast cereal or usual breakfast (control) groups. Setting: Free-living subjects aged 29 ± 71 y in Eastern Finland Subjects: 224 enrolled, 209 completed the study. The subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 14 publications
1
40
0
1
Order By: Relevance
“…This ®nding is in line with the results of several intervention (Kleemola et al, 1999) and observational (Stanton & Keast, 1989;Resnicow, 1991) studies in children and adults and may be explained by the negative correlation between breakfast cereal consumption and the percentage of energy from total and saturated fat. In our study the correlations between cereal intake and energyadjusted total and saturated fat intake were À0.281, P`0.001 and À0.186, P`0.001, respectively in boys, and À0.237, P`0.001 and À0.148, P 0.003 in girls.…”
Section: Discussionsupporting
confidence: 89%
“…This ®nding is in line with the results of several intervention (Kleemola et al, 1999) and observational (Stanton & Keast, 1989;Resnicow, 1991) studies in children and adults and may be explained by the negative correlation between breakfast cereal consumption and the percentage of energy from total and saturated fat. In our study the correlations between cereal intake and energyadjusted total and saturated fat intake were À0.281, P`0.001 and À0.186, P`0.001, respectively in boys, and À0.237, P`0.001 and À0.148, P 0.003 in girls.…”
Section: Discussionsupporting
confidence: 89%
“…Intervention studies involving the daily consumption of breakfast cereals have reported a 5-6% (unit percentage) decrease in food energy from fat with a corresponding 5-6% increase in energy from carbohydrate among college students 28 and Finnish adults 27 , and a 2.5% reduction in energy from saturated fat 27 . The lower fat intake associated with breakfast cereal consumption may explain the association of breakfast cereal consumption with reduced serum cholesterol levels in adults 27 . Previous analysis of the North/South Ireland Food Consumption data 65 showed that a high proportion (77%) of this adult population had mean daily intake below the recommended intake of 18 g of NSP 63 .…”
mentioning
confidence: 99%
“…Breakfast cereals are widely consumed, particularly in Ireland 16 , and a number of studies have shown an association between breakfast cereal consumption and replacement of food energy from fat with food energy from carbohydrate in adults 12,14,15,17 , adolescents and children 7,10,18,20,24,25 . Intervention studies in which breakfast cereals were introduced to the diet of adults led to a reduced intake of fat and an increased intake of carbohydrate 27,28 . The consumption of breakfast cereals has also been shown to be associated with lower serum cholesterol levels in adults 29 and children 25,30 .…”
mentioning
confidence: 99%
“…Intensive research has been concentrated on the quality of ready-to-eat cereal (RTEC) breakfasts and their impact on overall energy and nutrient intakes. These studies emphasise the low fat content and the high nutrient contents of RTEC breakfasts (20)(21)(22)(23)(24)(25) . Other types of breakfast, e.g.…”
mentioning
confidence: 99%